Introduced Predator Elicits Deficient Brood Defence Behaviour in a Crater Lake Fish - Lehtonen TK; McCrary JK; Meyer A (PUBLIC LIBRARY SCIENCE, 2022)
Introduced species represent one of the most serious global threats to biodiversity. In this field-based study, we assessed behavioural responses of brood tending cichlid fish to an invasive predator of their offspring. This was achieved by comparing parental defence responses of the endangered arrow cichlid (Amphilophus zaliosus), a fish species endemic to the crater lake Apoyo in Nicaragua, towards the bigmouth sleeper (Gobiomorus dormitor), a formidable predator of cichlid fry, and all other potential fish predators of offspring. The bigmouth sleeper was recently introduced into Apoyo but naturally co-exists with cichlids in a few other Nicaraguan lakes. Arrow cichlid parents allowed bigmouth sleepers to advance much closer to their fry than other predators before initiating aggressive brood defence behaviours. Interestingly, parents of a very closely related species, A. sagittae, which has coevolved with bigmouth sleepers in crater lake Xiloa, reacted to approaching bigmouth sleepers at comparable distances as to other predators of cichlid fry. These results provide a novel demonstration of the specific mechanism (i.e. naive parental behaviour) by which invasive predators may negatively affect species that lack the adequate behavioural repertoire.